2011
DOI: 10.1111/j.1748-7692.2011.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability and context specificity of narwhal (Monodon monoceros) whistles and pulsed calls

Abstract: The behavioral and environmental context of animal calls provides insights into their functions. Narwhals are a highly vocal species and, like other social cetaceans, rely on acoustic signals to communicate. We characterize and categorize narwhal whistles and pulsed calls, as well as investigate variation in these calls under different contexts (behavior, herd, and year) using recordings made during the month of August 2006–2008, in Koluktoo Bay (72°04′N, 80°32′W). We detected similarities among whistles but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
(128 reference statements)
2
38
0
Order By: Relevance
“…Clicks and whistles up to 24 kHz were first described [24, 25], with Watkins et al [24] acknowledging that they did not cover the full repertoire of narwhal. More recent studies using single receivers resulted in the description of whistles, pulsed calls, and clicks [26, 27]. Recordings with higher sampling rates revealed the true broadband nature of narwhal clicks where train clicks contained energy at above 100 kHz [28] and even extending above 200 kHz [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clicks and whistles up to 24 kHz were first described [24, 25], with Watkins et al [24] acknowledging that they did not cover the full repertoire of narwhal. More recent studies using single receivers resulted in the description of whistles, pulsed calls, and clicks [26, 27]. Recordings with higher sampling rates revealed the true broadband nature of narwhal clicks where train clicks contained energy at above 100 kHz [28] and even extending above 200 kHz [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mysticete calls are commonly detected at ranges of several tens of kilometres on a single hydrophone , while odontocete clicks and whistles can be detected at ranges of 1 -6 km (Quintana-Rizzo et al, 2006;Wang et al, 2006;Jensen et al, 2012;Ainslie, 2013). Stafford et al (2012a) and Marcoux et al (2012) discuss the large overlap in vocal repertoires of the two Monodontid species (beluga whales and narwhals) that share migration routes in Baffin Bay (Heide-Jørgensen et al, 2003a, c). To our knowledge, no studies have systematically discriminated between calls of these species.…”
Section: Introductionmentioning
confidence: 99%
“…Since narwhal pulsed and tonal signals (used for communication) and echolocation clicks (used for navigation and locating prey) are produced year-round (Marcoux, Auger-Méthé & Humphries 2011;Stafford, Laidre et al 2012), it is reasonable to postulate that the observed acoustic presence is a good proxy for overall occurrence of this species in the area. Furthermore, a recent study of narwhals tagged with short-term acoustic devices in coastal areas of East Greenland showed that narwhal pulsed and tonal signals were recorded most often when the animals were at depths of less than 100 m (Blackwell et al 2018), that is, within the same depth range as the hydrophone in the current study (75 m).…”
Section: Discussionmentioning
confidence: 99%
“…If visual inspection did not provide an unambiguous "yes/no" for acoustic presence, the corresponding sound files were listened to in order to classify the sounds correctly. Narwhals and white whales produce sounds within overlapping frequency ranges and therefore distinguishing between these two can be difficult if both species are present in acoustic recordings (Marcoux, Auger-Méthé & Humphries 2011;Stafford, Laidre et al 2012;Frouin-Mouy et al 2017). However, white whales are not known to occur in this area.…”
Section: Acoustic Data and Narwhal Signal Detectionsmentioning
confidence: 99%